Peningkatan Kapasitas Kolaborasi Tenaga Kesehatan Dalam Penanganan Kasus Kegawatdaruratan di Puskesmas - Munawaroh, Siti; Pamungkasari, Eti Poncorini; Randita, Amandha Boy Timor; Budiastuti, Veronika Ika; Hastami, Yunia; Maftuhah, Atik; Hermasari, Bulan Kakanita; Nugroho, Dian; Prabowo, Bima Kartika Yusuf; Rusyidi, Muhammad Andria (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2026)
Emergency care services at primary health care centers demand effective interprofessional collaboration to ensure patient safety and quality of care. However, the practice of interprofessional collaboration (IPC) in primary care still faces challenges due to limited role understanding and lack of team communication skills. This community engagement program aimed to improve the collaborative competencies of health workers at primary health care centers through case-based emergency simulation training. The clinical simulation was designed as a form of interprofessional education to build cross-professional coordination in responding to critical situations, while providing a safe and structured training environment. Evaluation was carried out through field observation and the Interprofessional Collaborative Competency Attainment Survey (ICCAS), which consists of 20 statements rated on a 7-point scale, where 1 indicates strong disagreement and 7 indicates strong agreement. The survey measured aspects of communication, shared decision-making, feedback, and role understanding among professions. The results showed that the simulation effectively enhanced health workers' preparedness to handle critical situations collaboratively. Most participants demonstrated increased scores in various aspects of collaborative competencies after the training. Case-based emergency simulation has the potential to become a relevant learning approach to strengthen team collaboration skills in primary care, while supporting the emergency response system at the community level.